Participatory Approaches to Country Assistance Strategies : Lessons from Africa - Boyd, Barbara L.; Stokes, Ellery; Edgerton, Jim; Donnelly-Roark, Paula; Reinikka, Demba; Kasozi, Mary (World Bank, Washington, DC, 2012)
This note focuses on the experiences, in four African countries, of using participatory approaches to allow borrower counterparts and civil society groups, to influence country assistance strategies (CAS) priorities. While it is demonstrated that each process needs to be tailored to the specific situation of a given country at a particular time, it also highlights significant commonalities. Cases are compared in Kenya, where the current CAS is focused on public sector reform in response to civil society demands, and in Sierra Leone, where the CAS process assisted the Government in ascertaining the development priorities of local stakeholders, during the hardships of post-conflict instability, as well as comparisons in Senegal, and Uganda. The reasons for undertaking CASs in a participatory manner include improving the Bank understanding of the CAS document, by tapping into local knowledge to ensure community concerns, and, helping to increase transparency, and public understanding of Bank/government partnerships, in addition to enhancing stakeholder participation in lending, and non-lending operations, including implementation of CASs. Recommendations for this participatory approach suggest supportive country teams, ensuring the understanding of implications by senior borrower counterparts, committed to this approach, and utilizing early strategic planning, and processing.